A descoberta das correntes neutras das interações fracas - Fortes, E. C.F.S. [UNESP]; Tijero, M. C.; Pleitez, Vicente [UNESP] (My University, 2007)
In this paper we narrate the discovery of the weak neutral currents by two independent experimental collaborations. We also give a brief review of the history of the neutral currents in order to give a clear description of the context of that discovery which was decisive for a later confirmation of the electroweak standard model. This discovery shows the difficulty for considering the experimental results as being completely independent of the theory.
The discovery of the weak interactions's neutral currents
Keywords: Electroweak model; Neutral currents; Z boson